2015
DOI: 10.1075/lab.5.3.01hen
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic analysis of the rhotic contrast in Chicagoland Spanish

Abstract: This paper reports on an acoustic analysis of the phonemic tap-trill contrast (/ɾ/-/r/) for first and second generation speakers of Mexican Spanish who live in the Chicagoland area. First, it is shown that speakers most commonly produce phonemic trills with a single apical occlusion, although there is much individual variation. Second, nearly all speakers realize the tap-trill contrast by means of segmental duration, and this is especially true for speakers who favor zero or one closures in the phonemic trill.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 54 publications
3
46
0
Order By: Relevance
“…The native bilingual and Chicagoland HL user data presented by Henriksen shows considerable variation, but in general the Spanish contrast is maintained through segment length rather than vibrations, and is not attributed to English influence. Amengual's (forthcoming) results on HL users and L2 learners generally reflect Henriksen's (2015) findings.…”
Section: Consonantsmentioning
confidence: 54%
See 1 more Smart Citation
“…The native bilingual and Chicagoland HL user data presented by Henriksen shows considerable variation, but in general the Spanish contrast is maintained through segment length rather than vibrations, and is not attributed to English influence. Amengual's (forthcoming) results on HL users and L2 learners generally reflect Henriksen's (2015) findings.…”
Section: Consonantsmentioning
confidence: 54%
“…In particular, the more recent study highlights the fact that in the data presented, /b/ distinguishes itself from /dg/ in terms of demonstrating patterns that diverge the most from native tendencies. Finally, Henriksen (2015) is the first study to address rhotic phonemes in the Spanish of HL users. The tap /ɾ/, which is described as a single vibration created by the tongue tip contacting the alveolar ridge, is a phoneme in Spanish that contrasts intervocalically with the trill /r/, which is characterized by a series of the same type of vibration (Hualde, 2005).…”
Section: Consonantsmentioning
confidence: 99%
“…3 One feature known to distinguish trills from taps is their duration (Henriksen, 2015). The taps in our stimuli were indeed shorter than the trills (33 ms vs 63 ms; t(31) ¼ 10.23, p < 0.001).…”
Section: Stimulimentioning
confidence: 81%
“…With the goal to account for adult Spanish heritage speakers' divergent trill production from the monolingual norms (Amengual, 2016;Kissling, 2018;Henriksen, 2015), the present study adopted a developmental approach by directly comparing child and adult heritage speakers. We then compared our findings to those of non-heritage native speakers reported in other studies (Bradley & Willis, 2012;Carballo & Mendoza, 2000;Henriksen, 2015;Lastra & Martín Butragueño, 2006;Kissling, 2018). While both the adult heritage speakers and the child heritage speakers showed divergence from the non-heritage native baselines in one or more phonetic properties of the trill, the adult heritage speakers produced the trill in a more target-like manner than the child heritage speakers (CHS < AHS).…”
Section: Connecting the Dots Between Child And Adult Heritage Speakermentioning
confidence: 99%
“…4 With regard to long-term Mexican immigrants, Henriksen (2015) found that more than half of the trills had zero or one occlusion. Although allophonic distribution of nonnormative trills was not the main focus of the study, Henriksen (2015) reported that the variants with zero occlusion were primarily fricatives. Moreover, based on the findings in Henriksen (2015), in which the speakers who mainly produced the trills with one occlusion demonstrated significantly longer duration than the phonological taps, it is likely that the trill variants with one occlusion were taps followed by vocalic r-coloring or frication, similar to those in Bradley and Willis (2012).…”
Section: Connecting the Dots Between Child And Adult Heritage Speakermentioning
confidence: 99%